Understanding the perspectives of older adults and elderly regarding vaccination; a snapshot in four European countries. (13th November 2019) - Timen, A; Eilers, R; Lockhart, S; Gavioli, R; Paul, S; Volo, S
Abstract: Prevention of infectious diseases in elderly by immunization is a prerequisite to ensuring healthy ageing. However, in order for the vaccine programs to be effective, these need to be provided by health care professionals who have up-to-date knowledge and high motivation. Furthermore, the knowledge and attitudes towards vaccination in the targeted age groups needs to be fully understood. When focusing on the information provision, it is important to know from whom or which institution older adults and elderly would like to receive and in which form. In January 2019, an international project called the VITAL (The Vaccines and InfecTious diseases in the Ageing population) project was started, within the framework of IMI (Innovative Medicines Initiatives). One of the goals of the VITAL project is to develop strategies to educate and train health care professionals (HCPs) and to promote awareness among stakeholders involved in elderly care management. We briefly focus on the results of studies undertaken in four European countries (Italy, France, The Netherlands and Hungary), which reveal the perspective of older adults and elderly regarding influenza, pneumococcal, herpes zoster vaccination and respiratory syncytial virus (RSV) as well as generic characteristics of the vaccines and diseases. We will show how attitudes towards vaccination are represented in our study population and which determinants influence the decision-making process of accepting vaccination. Furthermore, we shall elaborate on how the decision-making process towards vaccination takes place and which additional information is needed. In the second part of the session, we shall invite the audience to reflect on the findings and identify the factors they consider most important for setting up a training and education programme on vaccination.